Feed additives supplementation: A potential strategy to ameliorate heat stress in sheep - Binuni Rebez, E.; Sejian, V.; Silpa, M. V.; Kalaignazhal, G.; Devaraj, C.; Nikhil, K. T.; Ninan, J.; Tüfekci, H.; Fonsêca, V. F.C. [UNESP]; Chauhan, S. S.; Digiacomo, K.; Dunshea, F. R.; et al. (De Gruyter, 2024)
Given a significant climate-flexible and socio-economic role in developing nations, environmental heat stress imposes a major financial impact on sheep production systems globally endangering their production, reproduction, and growth. In this regard, the adverse effects of heat stress on sheep production systems have to be addressed through adoption of effective heat alleviation measures like animal management, nutritional management and genetic interventions of which the nutritional interventions seems to be the most cost effective way to alleviate heat stress. Nutritional manipulation for heat stress alleviation in sheep involves the use of antioxidant supplements (Vitamin B; Vitamin E and Selenium; Selenium; Zinc sulphate and folic acid; Vitamin C, Vitamin E, Selenium and Zinc; Naringin; Opuntia ficus-indica f. inermis; Açai oil and Brown seaweed like Ascophyllum nodosum and Sargassum latifolium). Further, electrolyte supplements (Dietary Electrolyte Balance (DEB); Sodium bicarbonate and potassium bicarbonate; Sodium hydroxide) have a beneficial effect on thermal responses, respiratory activities, gas exchange parameters, rumen fermentation, blood buffering capacity and acid-base balance. The mineral mixture supplements (Mineral blocks; Mineral mixture and antioxidants; Chromium; Zinc) play a crucial role in increasing the efficiency of antioxidant defence system, immunity-related parameters, production, reproduction, feed digestibility and insulin sensitivity. Probiotic supplements (Lactobacillus acidophilus, Saccharomyces cervisiae, Propionibacterium freudenreichii, Lactobacillus casei, Enterococcus faecium, Lactobacillus lactis, Bacillus subtilis, Propionibacterium freudenreichii, Pediococcus cerevisiae, Megaspha eraelsdenii, Bacillus licheniformis, Aspergillus oryzae, Schizochytrium limacinum, Trichoderma reesei and Saccharomyces cerevisiae) improve lactational performance, dietary energy utilization and productivity. The probiotics (live Saccharomyces cerevisiae) and prebiotics (mannan oligosaccharide plus b-glucans) used in heat stress alleviation improve dietary energy utilisation. Furthermore, the vital role of herbal supplements (Rosemary, Cinnamon, Turmeric, Clove, Naringin, Chestnut tannins, Giloy stem powder, Curcumin, Rocket oil (watercress oil), Flaxseed, Cornus, Oregano, Thyme, Chamomile flowers, Moringa oleifera, Betaine) has been highlighted to promote feed intake, antioxidant status, growth performance, feed utilization, reproductive performance and immune response. Effective adoption of nutritional strategies can thus ensure sustainable sheep production in this changing climate scenario.
Keywords: climate change; feed supplements; heat stress; mitigation approach; sheep husbandry; sustainability